Liver X Receptor Regulation of Thyrotropin-Releasing Hormone Transcription in Mouse Hypothalamus Is Dependent on Thyroid Status - Ghaddab-Zroud, Rym (Public Library of Science, 2014)
Reversing the escalating rate of obesity requires increased knowledge of the molecular mechanisms controlling energy balance. Liver X receptors (LXRs) and thyroid hormone receptors (TRs) are key physiological regulators of energetic metabolism. Analysing interactions between these receptors in the periphery has led to a better understanding of the mechanisms involved in metabolic diseases. However, no data is available on such interactions in the brain. We tested the hypothesis that hypothalamic LXR/TR interactions could co-regulate signalling pathways involved in the central regulation of metabolism. Using in vivo gene transfer we show that LXR activation by its synthetic agonist GW3965 represses the transcriptional activity of two key metabolic genes, Thyrotropin-releasing hormone (Trh) and Melanocortin receptor type 4 (Mc4r) in the hypothalamus of euthyroid mice. Interestingly, this repression did not occur in hypothyroid mice but was restored in the case of Trh by thyroid hormone (TH) treatment, highlighting the role of the triiodothyronine (T(3)) and TRs in this dialogue. Using shLXR to knock-down LXRs in vivo in euthyroid newborn mice, not only abrogated Trh repression but actually increased Trh transcription, revealing a potential inhibitory effect of LXR on the Hypothalamic-Pituitary-Thyroid axis. In vivo chromatin immunoprecipitation (ChIP) revealed LXR to be present on the Trh promoter region in the presence of T(3) and that Retinoid X Receptor (RXR), a heterodimerization partner for both TR and LXR, was never recruited simultaneously with LXR. Interactions between the TR and LXR pathways were confirmed by qPCR experiments. T(3) treatment of newborn mice induced hypothalamic expression of certain key LXR target genes implicated in metabolism and inflammation. Taken together the results indicate that the crosstalk between LXR and TR signalling in the hypothalamus centres on metabolic and inflammatory pathways.